Individualized dupilumab therapy in the treatment of pediatric patients with severe atopic dermatitis: Case series in a Malaysian Tertiary Center - Wai Quen Lee; Siti Nuraihan Nordin; Sabeera Begum Kader Ibrahim; Kin Fon Leong (Wolters Kluwer Medknow Publications, 2022)
To look at patient characteristics, response to dupilumab, and adverse events due to treatment. This was a retrospective review of all pediatric patients on dupilumab and topical corticosteroids for severe atopic dermatitis in Paediatric Dermatology Clinic, Women and Children Hospital, Kuala Lumpur, from 2020 to 2021. In this cohort, 50% achieved Eczema area and severity index (EASI) -75 by week 12, 25% at week 16, and 25% at week 56. Three of four patients achieved EASI-75 at a median of 12 weeks of treatment, despite not receiving loading doses of dupilumab. None of our patients had conjunctivitis or upper respiratory tract infection while treated with dupilumab. In conclusion, dupilumab is a safe and effective drug to induce remission in severe pediatric eczema, without undesirable side effects in our cohort. In a resource-limited setting, individualized treatment regimen without loading doses is as effective as fixed-dose regimens with loading doses to achieve EASI-75.